High-velocity impact behaviour of aluminium honeycomb sandwich panels with different structural configurations - Sun, Guangyong; Chen, Dongdong; Wang, Hongxu; Hazell, Paul J.; Li, Qing (International journal of impact engineering, 2018)
•Increasing facesheet thickness caused smaller deformation depths but larger deformation areas.•Core height had a small effect on the ballistic limit velocity of sandwich panels.•Front facesheet failed more easily due to stress concentration with the increase of core stiffness.•The increase of front-to-back thickness ratio led to higher damage resistance.•A structural optimisation for maximising the specific energy absorption was presented. This paper presents a combined experimental and numerical study on the dynamic response and failure mechanisms of honeycomb sandwich panels subjected to high-velocity impact by a spherical steel projectile. Impact tests were performed in a velocity range from about 70 to 170 m/s to investigate the effects of facesheet thickness, core height, cell wall thickness and cell size of honeycomb on the impact behaviour of sandwich panels. These geometric parameters were found to influence the impact performance mainly by changing the deformation and failure mechanisms of both sandwich facesheets. Moreover, the ballistic limit velocity and critical perforation energy of each sandwich configuration were obtained by numerical simulation. It was found that increasing facesheet thickness and reducing honeycomb cell size were two weight-efficient ways to enhance the perforation resistance of sandwich panels when the areal density exceeded a certain value. The projectile's penetration process into the sandwich panel and the associated energy absorbing mechanisms were analysed, the results of which showed that facesheets contributed most to energy absorption. Further numerical simulation was conducted to explore the influences of core stiffness and the thickness ratio of front to back facesheet. It was found that core stiffness had a significant effect on the deformation and failure initiation of front facesheet; more specifically, the front facesheet failed more easily due to stress concentration with the increase of core stiffness. When the total thickness of front and back facesheets remained constant, increasing the front-to-back thickness ratio led to higher damage resistance but greater deformation area on the front facesheet. Finally, a discrete optimisation was conducted to generate an optimal design of sandwich structure for achieving the highest specific energy absorption without perforation under a certain impact energy. The optimised sandwich panel exhibited an increase of 23.7% in specific energy absorption compared with the initial design.